Почему непонятен «Цвет граната»? - Закоян, Гарегин (ՀՀ ԳԱԱ «Գիտություն» հրատ.)
Отвечая на вынесенный в заголовок вопрос – «Почему непонятен "Цвет граната"?», автор исходит из идеи несоответствия исторически сложившейся понятийно-словесной модели (знак и значение) восприятия фильма (повествовательное кино) и положенной в основу «Цвета граната» поэтической модели (автономно созерцаемый образ-смысл), принципиально не функционирующей в парадигме понятийно-словесной модели. Речь идет о внесловесном киномышлении, аналогичном, к примеру, мышлению музыкальному. Վերնագրում շարադրված «Ինչու՞ է «Նռան գույնն» անհասկանալի» հարցին պատասխանելով հեղինակը ելնում է ֆիլմի ըմբռն-ման պատմականորեն կայացած մտածական-բառային կաղապարից (նշան և նշանակություն) և «Նռան գույնի» հիմք ծառայած պոետիկ կաղապարի (ինքնուրույնորեն զննվող կերպարիմաստ), որն սկզբունքորեն չի գործում մտածական-բառային կաղապարի աղյուսակում։ To answer the question in the title – “Why is The Color of Pomegranates not understandable?”, the author proceeds from the idea of discrepancy between the historically established conceptual-verbal model (sign and meaning) of film perception (narrative cinema), and the poetic model (autonomously contemplated image-meaning), laid in the basis of The Color of Pomegranates, which fundamentally does not function in the paradigm of the abovementioned conceptual-verbal model. Here, the “beyond verbal” cinema thinking is meant, identical, for instance, to musical thinking.
Keywords: Искусствоведение